The RNA‐binding protein HuR/ELAVL1 regulates IFN‐β mRNA abundance and the type I IFN response. Issue 5 (12th March 2015) - Herdy, Barbara; Karonitsch, Thomas; Vladimer, Gregory I.; Tan, Chris S.H.; Stukalov, Alexey; Trefzer, Claudia; Bigenzahn, Johannes W.; Theil, Tamara; Holinka, Johannes; Kiener, Hans P.; Colinge, Jacques; Bennett, Keiryn L; et al.
<x xml:space="preserve">Abstract</x> Secretion of type I interferon (IFN) is the first cellular reaction to invading pathogens. Despite the protective function of these cytokines, an excessive response to their action can contribute to serious pathologies, such as autoimmune diseases. Transcripts of most cytokines contain adenylate‐uridylate (A/U)‐rich elements (AREs) that make them highly unstable. RNA‐binding proteins (RBPs) are mediators of the regulatory mechanisms that determine the fate of mRNAs containing AREs. Here, we applied an affinity proteomic approach and identified lethal, abnormal vision, drosophila‐like 1 (ELAVL1)/Hu antigen R (HuR) as the predominant RBP of the IFN‐β mRNA ARE. Reduced expression or chemical inhibition of HuR severely hampered the type I IFN response in various cell lines and fibroblast‐like synoviocytes isolated from joints of rheumatoid arthritis patients. These results define a role for HuR as a potent modulator of the type I IFN response. Taken together, HuR could be used as therapeutic target for diseases where type I IFN production is exaggerated.